Small Lesion Size Is Associated with Sleep-Related Epilepsy in Focal Cortical Dysplasia Type II - Jin, Bo; Hu, Wenhan; Ye, Linmei; Krishnan, Balu; Aung, Thandar; Jones, Stephen E.; Najm, Imad M.; Alexopoulos, Andreas V.; Zhang, Kai; Zhu, Junming; Zhang, Jianguo; Ding, Meiping; et al. (Frontiers in Neurology, 2018)
Objective: To investigate the neuroimaging and clinical features associated with sleep related epilepsy (SRE) in patients with focal cortical dysplasia (FCD) type II. Methods: Patients with histopathologically proven FCD type II were included from three epilepsy centers. SRE was defined according to the video-EEG findings and seizure history. Cortical surface reconstruction and volume calculation were performed using FreeSurfer. The lesions were manually delineated on T1 volumetric MRI using the ITK-SNAP software. The lesion volumes were normalized by the intracranial volume of each patient. The lesions were classified as small or large by placing a threshold based on quantitative (whether the lesion was detected on MRI report) and qualitative (volume) criteria. Results: A total of 77 consecutive patients were included. Of them, 36 had SRE and 41 had non-SRE. An earlier age of epilepsy onset, high seizure frequency, regional interictal EEG findings and favorable surgical outcome were characteristic in both groups. Small lesions were defined as those having a volume < 3217 mm3. In total, 60.9% of the patients with SRE (25/41) had small FCD lesion, which was significantly higher than the non-SRE group (9/34, 26.5%, p=0.005). Small lesion size was the only predictor significantly associated with SRE in the overall type II group by multivariate analyses (p=0.016). Although the proportion of patients who had frontal FCD and SRE was higher than non-frontal FCD (54.5% vs. 27.3%, p=0.043), the relationship between SRE and lesion location was not confirmed by multivariate analysis. Thalamic volume and seizure semiology were not statistically different between the SRE and non-SRE group. The significant association between lesion size and SRE was reproducible in type IIb and IIa subgroups. Significance: SRE is common in patients with FCD type II. Small FCD type II lesions are significantly associated with SRE. Although our findings cannot be applied to the entire spectrum of SRE, potential existence of small FCD lesions should be considered when evaluating patients with SRE, and utilization of all other supportive electroclinical information for lesion detection is highly desirable.